(?, ?) -Statistical Convergence on a Product Time Scale - Cinar, Muhammed; Yilmaz, Emrah; Altin, Yavuz; Et, Mikail (Univ Punjab, Dept Mathematics, 2019)
We give definition of (lambda,nu)(-) statistical convergence on a product time scale. Furthermore, we generalize de la Vallee Poussin mean and define strongly (V,lambda,nu) and [V,lambda,nu](psi 2)(p)(-) summable functions, statistical limit superior and inferior on a product time scale. Then, a few inclusion relations are expressed between the sets of (V,lambda,nu)(-)summable, (p-)strongly [V,lambda,nu](psi 2)(p)(-)summable and (lambda,nu)(-)statistical convergent functions. Furthermore, some theorems are proved related to statistical limit superior and inferior on a product time scale.
Keywords: Statistical convergence; Time scale; Summability